2020
DOI: 10.3390/electronics9060938
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Fault-Tolerant Control of Multiphase Induction Machines: A Game Changer

Abstract: Until very recently, the fault tolerance in multiphase electric drives could only be achieved after fault localization and a subsequent modification of the control scheme. This scenario was profoundly shaken with the appearance of the natural fault tolerance, as the control reconfiguration was not required anymore. Even though the control strategy was highly simplified, it was still necessary to detect the open-phase fault (OPF) in order to derate the electric drive and safeguard its integrity. This work goes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
(35 reference statements)
0
17
0
2
Order By: Relevance
“…However, three nonconventional solutions for voltage control of variable-speed induction generators were proposed in [16,20,21]. The multiphase induction and synchronous generators can produce the output voltage at broken phase connections tolerating the machine or converter damages [17,22,23].…”
Section: Application Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three nonconventional solutions for voltage control of variable-speed induction generators were proposed in [16,20,21]. The multiphase induction and synchronous generators can produce the output voltage at broken phase connections tolerating the machine or converter damages [17,22,23].…”
Section: Application Suggestionsmentioning
confidence: 99%
“…Multiphase induction machines with the second type of winding can practically work at the supply sequence number m = 1. Such a machine can be designed with almost sinusoidally distributed windings, having all the advantages of fault tolerance of multiphase induction machines [4,17,22,23,25,26].…”
Section: Induced No-load Voltagementioning
confidence: 99%
“…A proposed idea of a passive or natural fault tolerance has been presented in [10][11][12][13]. It is demonstrated that it is possible to develop a drive control algorithm which should not be re-configured after a fault occurs (i.e., the current reference values will be automatically adjusted in the post-fault operation mode).…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, when three phase induction machines are interfaced with conventional multi-step inverter then the pulsating component of torque are appearing in the machine and due to this pulsating torque, the vibrations are appearing in to machine. 2,3 The generators are widely utilized by renewable power industries for wind energy generation system (WEGS) and for establishing continuous power production using DFIG during the faults, the main requirements 4,5 for the DFIG system include the following:…”
Section: Introductionmentioning
confidence: 99%
“…The generators are widely utilized by renewable power industries for wind energy generation system (WEGS) and for establishing continuous power production using DFIG during the faults, the main requirements 4,5 for the DFIG system include the following: High Reliability: The reliability of the generator should be high. With the help of a reliable DFIG system, the interruption due to fault can be mitigated. Fast response: The response of the machine should be as fast as possible by keeping minimum plant down time. Lower pulsating torque: The pulsating torque of DFIG should have as lower as possible during six step inverters feeding. …”
Section: Introductionmentioning
confidence: 99%